From "disinterested" education to «“philosophy of praxis" or "neo-humanism”» - Pirotta, Sebastiano (International Gramsci Journal, 2025)
The article deals with Gramsci’s pedagogical reflection, starting from the analysis of some early writings in which the need to develop a militant and “disinterested” proletarian culture emerges. The concept of “disinterestedness” is constantly used, through a series of lexical variants, from 1915 until the Prison Notebooks. In particular, after the famous reference to Goethe’s «für ewig» in the letter to Tatiana of 19 March 1927, this theme gradually resurfaces in a series of notes dedicated to the hegemonic-pedagogical role of intellectuals and the school. More specifically, particular attention is given at first to the influence of neo-idealist pedagogy (Giuseppe Lombardo Radice and Salvemini) on the early writings of the Sardinian intellectual. The analysis then focuses on new semantic contributions that contribute to the inclusion of the pedagogical discourse within the prison reflection on the «philosophy of praxis».